2018
DOI: 10.3390/f9040209
|View full text |Cite
|
Sign up to set email alerts
|

Stock Volume Dependency of Forest Drought Responses in Yunnan, China

Abstract: Abstract:Revealing forest drought response characteristics and the potential impact factors is quite an important scientific issue against the background of global climate change, which is the foundation to reliably evaluate and predict the effects of future drought. Due to the high spatial heterogeneity of forest properties such as biomass, forest age, and height, and the distinct differences in drought stress in terms of frequency, intensity, and duration, current studies still contain many uncertainties. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
(98 reference statements)
2
18
0
Order By: Relevance
“…Our results showed that regional mean RWI was reduced from an average of 1,033 to 970 (Figure 3d), which is comparable to the studies of interannual legacy effects from Anderegg et al (2015) and Wu et al (2017). Previous studies reported that correlations between vegetation indices (e.g., RWI, NDVI) and drought indices (e.g., SPEI) were tested significant at a timescale over 24 months Luo et al, 2018;Vicente-Serrano et al, 2014). Nevertheless, even when the previous hydrological year was under extreme drought conditions, its impact on current year RWIs were much less than the impact from drought in the current hydrological…”
Section: Tree Stem Radial Growth Responses To Drought Dimensionssupporting
confidence: 89%
See 3 more Smart Citations
“…Our results showed that regional mean RWI was reduced from an average of 1,033 to 970 (Figure 3d), which is comparable to the studies of interannual legacy effects from Anderegg et al (2015) and Wu et al (2017). Previous studies reported that correlations between vegetation indices (e.g., RWI, NDVI) and drought indices (e.g., SPEI) were tested significant at a timescale over 24 months Luo et al, 2018;Vicente-Serrano et al, 2014). Nevertheless, even when the previous hydrological year was under extreme drought conditions, its impact on current year RWIs were much less than the impact from drought in the current hydrological…”
Section: Tree Stem Radial Growth Responses To Drought Dimensionssupporting
confidence: 89%
“…(). Previous studies reported that correlations between vegetation indices (e.g., RWI, NDVI) and drought indices (e.g., SPEI) were tested significant at a timescale over 24 months (Li et al., ; Luo et al., ; Vicenteā€Serrano et al., ). Nevertheless, even when the previous hydrological year was under extreme drought conditions, its impact on current year RWIs were much less than the impact from drought in the current hydrological year (Figure c).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As climate change becomes unavoidable, more attention and effort are called for reducing the impact of drought on forest ecosystems. Our results showed that forest responses to climate were also affected by tree size [ 51 , 52 , 53 ], which sheds new light on managing forests under the changing climate. Although the economic benefits and ecosystem services of trees increase with their size over time, the risk of mortality or dieback under drought stress also increases with time.…”
Section: Discussionmentioning
confidence: 91%